2010
DOI: 10.1371/journal.pgen.1001006
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin Is Limiting for the Suppression of DNA Damage–Induced Recombination between Homologous Chromosomes

Abstract: Double-strand break (DSB) repair through homologous recombination (HR) is an evolutionarily conserved process that is generally error-free. The risk to genome stability posed by nonallelic recombination or loss-of-heterozygosity could be reduced by confining HR to sister chromatids, thereby preventing recombination between homologous chromosomes. Here we show that the sister chromatid cohesion complex (cohesin) is a limiting factor in the control of DSB repair and genome stability and that it suppresses DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 56 publications
6
81
0
Order By: Relevance
“…The examined markers correlated with each other, partially unraveling the network of genes involved in endometrial tumorigenesis. Findings of previous studies have suggested that the decreased expression of cohesins results in an inappropriate increase in homologous recombination which may drive tumorigenesis through the promotion of genomic instability, such as loss of heterozygosity (15,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The examined markers correlated with each other, partially unraveling the network of genes involved in endometrial tumorigenesis. Findings of previous studies have suggested that the decreased expression of cohesins results in an inappropriate increase in homologous recombination which may drive tumorigenesis through the promotion of genomic instability, such as loss of heterozygosity (15,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…7, 33 Recently, we found that by events without associated crossovers. For example, sequential repair of two UV lesions found on opposite strands but distant from each other may result in a 4:0 ratio.…”
Section: Uv Lesions and Uv-induced Recombinationmentioning
confidence: 99%
“…Although cohesin is required for recombinational repair of DSBs in G 2 , cells are capable of repair at a semi-permissive temperature. 33 Overnight cultures grown at permissive temperature (23°C) were diluted and grown to logarithmic phase at permissive (green in Fig. 3), or semi-permissive temperature, 30°C (red in Fig.…”
Section: Uv Initiation and Completion Of Recombination Is Revealed Inmentioning
confidence: 99%
“…Cohesin is essential for DNA repair and chromosome segregation [1,2]. Heterozygous cohesin mutations are the cause of multi-systems developmental disorder such as Cornelia de Lange syndrome [3][4][5], and cohesin mutations have also been reported in cancer [6][7][8].…”
Section: Overviewmentioning
confidence: 99%
“…Aptly named 'SMC' proteins for 'structural maintenance of chromosomes' cohesin, condensin and Smc5/6 complexes maintain the integrity of genetic information by enabling postreplicative DNA repair, shaping chromosomes in preparation for cell division, and holding sister chromatids together to ensure that daughter cells receive a full complement of chromosomes.Cohesin is essential for DNA repair and chromosome segregation [1,2]. Heterozygous cohesin mutations are the cause of multi-systems developmental disorder such as Cornelia de Lange syndrome [3][4][5], and cohesin mutations have also been reported in cancer [6][7][8].…”
mentioning
confidence: 99%